2013
DOI: 10.1002/lt.23670
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of liver graft washout as a function of the perfusate, pressure, and temperature

Abstract: Donor graft washout can be impaired by colloids in organ preservation solutions that increase the viscosity and agglutinative propensity of red blood cells (RBCs) and potentially decrease organ function. The colloid-induced agglutinative effects on RBCs and RBC retention after liver washout with Ringer's lactate (RL), histidine tryptophan ketoglutarate solution, University of Wisconsin solution, and Polysol were determined as a function of the washout pressure (15 or 100 mm Hg) and temperature (4 or 37 C) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…the removal of blood components from the microvasculature during liver retrieval, may affect subsequent graft injury and function [76,77]. Numerous parameters related to graft washout in transplantation settings might influence its efficacy in removing blood cells: (1) type of solution (colloid content, viscosity) [78]; (2) temperature (hypothermic or normothermic washout) [79]; (3) high or low washout pressure/speed (shear stress) [76,80,81]; (4) washout time [77]; (5) heparinization [82,83], and (6) way of washout (portal venous, arterial, or simultaneous) [77]. …”
Section: Technical Issues Concerning P-olt In Ratsmentioning
confidence: 99%
“…the removal of blood components from the microvasculature during liver retrieval, may affect subsequent graft injury and function [76,77]. Numerous parameters related to graft washout in transplantation settings might influence its efficacy in removing blood cells: (1) type of solution (colloid content, viscosity) [78]; (2) temperature (hypothermic or normothermic washout) [79]; (3) high or low washout pressure/speed (shear stress) [76,80,81]; (4) washout time [77]; (5) heparinization [82,83], and (6) way of washout (portal venous, arterial, or simultaneous) [77]. …”
Section: Technical Issues Concerning P-olt In Ratsmentioning
confidence: 99%
“…[41][42][43] Prior studies in human livers have also shown that initial warm LR ush results in the least RBC retention, challenging the long-held belief of cold washout as the rst step in liver procurement. [19] However, a limitation of this work is that the rate of cooling effect in rat livers with an in-situ ush is much faster compared to other animal models with larger livers. Using cold ush solutions for the purpose of metabolic depression leverages the fact that tissue deterioration slows down at decreasing temperatures.…”
Section: Discussionmentioning
confidence: 95%
“…Post et al showed that ushing with warm lactated ringers (LR) resulted in less RBC retention and shorter washout times compared to cold UW and histidine tryptophan ketoglutarate (HTK) ushes. [19] Additional studies demonstrated that the high potassium concentration in UW solution combined with cold temperature resulted in vasoconstriction, [20] and the high viscosity of UW lead to poor initial reperfusion of the liver graft due to RBC aggregation. [21] Prior literature has shown that the interacting factors of cold temperature, solution composition, and viscosity of ushing solutions interact to in uence donor blood cell retention/aggregation as well as allograft physiology.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, the “fate” of a unit of pRBCs transfused into a deceased donor just prior to organ procurement is electronically linked to the deceased donor, rather than the recipient of those organs, even though a very small volume of the third‐party blood donor's pRBCs is likely to be transferred to the organ recipient(s) 10 . In contrast, a unit of pRBCs used on ex situ NMP can either be “fated” to the organ itself, or to the organ recipient.…”
Section: Administration and Traceabilitymentioning
confidence: 99%
“…After undergoing ex situ NMP, organs are flushed with cold preservation solution before being implanted. Although cold flushing will remove the vast majority of red blood cells within the organ, small numbers remain 10 . These residual red blood cells may cause biologically significant effects 11 .…”
Section: Introductionmentioning
confidence: 99%